Letter - Shanley, J. R.
012b-0065-001 AMALGAMATED UNION OF UPHOLSTERERS OF GREAT BRITAIN AND IRELAND Affiliated to: Trades Union Congress Scottish Trades Union Congress Phone—TERminus 5216 Affiliated to: Labour Party General Federation of Trade Unions J. R. SHANLEY, Gen. Secretary, Swinton House, 324 Gray's Inn Road, London, W.C.1 Ref. JRS/DS. January 21st. 1939. The Secretary, Trades Union Congress, Transport House, SMITH SQUARE. S.W.1. Dear Sir, The Executive Committee of the A.U.U. have been informed by the I. P. C. Spain Committee that you have considered it necessary to decline to meet the Deputation arranged for Tuesday, 24th. January 1939. Whilst appreciating the reasons given for this attitude, they would ask that in view of the serious position in Spain, that further consideration be given to the question. Yours faithfully, J.R. Shanley General Secretary 292/946/12b/65